Ticagrelor: Long-Term Therapy in Patients with Coronary Artery Disease - Rognoni, Andrea; Cavallino, Chiara; Lupi, Alessandro; Bacchini, Sara; Rosso, Roberta; Rametta, Francesco; Nardi, Federico; Sante Bongo, Angelo (Reviews on Recent Clinical Trials, 2016)
Introduction: Atherothrombosis and coronary artery disease affect more than 13 million individuals only in the United States, about 8 millions in Europe and are the major causes of death worldwide. In particular chronic stable angina impairs patient quality of life, is associated with an important health spending and increased patient mortality; it is a prominent symptom of coronary artery disease (CAD), the latter being prevalent worldwide in patients. A key role in pathophysiology of cardiovascular acute events is played by activated platelets. Aspirin and adenosine diphosphate antagonist in addition to it is recommended for 1 year for reduction of cardiovascular events in patients with prior myocardial infarction with a weak recommendation to continue thereafter. P2Y12 receptor antagonists, in addition to aspirin, have been shown in the last years, to reduce ischemic events in patients with acute coronary syndrome but their role in secondary prevention is still new and unclear. The aim of our paper is to review the long-term effect of therapy with ticagrelor on the basis of recent evidence based data. Methods: We performed an online search on the major search engines. All the randomized controlled trials were summarized in the table. Results: We included in our paper six randomized controlled trials and we mentioned about ten post – hoc analysis, sub studies and registries. All studies included the type the therapy and a mid or long term clinical follow up. Conclusions: The studies reported in our paper and in particular PEGASUS – TIMI 54 study showed the merit to placing attention of prevention secondary ischemic events after acute coronary syndrome in the context of treatment with dual anti – platelet therapy; it proved a clinical benefit in patients treated with ticagrelor (60 mg x 2) for 3 years. Nevertheless, the effectiveness of these results cannot be generalized to patients with higher bleeding risk or low ischemic risk. In fact prolonged therapy with ticagrelor 60 mg in combination with aspirin could be considered valuable in patients with repeated acute ischemic events or with several coronary revascularizations over time (especially in patients with lower bleeding risk).
Keywords: Acute coronary syndromes